Synergistic coupling of hybrid h-BN and expanded graphite in thermal conductive coating for radiative cooling - Cheong, Khai Feng (Nanyang Technological University, 2022)
The adverse impacts of climate change have been becoming increasingly apparent over the years, in particular global warming. Increasing global temperatures have led to the use of Heating, Ventilation, and Air-Conditioning (HVAC) systems for cooling, which further accelerates global warming. Radiative cooling offers a passive method for cooling that has been drawing increased attention due to its energy-saving potential and environmentally friendly nature. Current approaches to radiative cooling either increased the effectiveness of the material to emitted thermal radiation by adding thermally emissive materials or by decreasing the amount of incoming solar radiation absorbed through the incorporation of materials that are solar reflective. This study evaluated the potential of the concurrent use of both thermally emissive Expanded Graphite (EG) and solar reflective hexagonal boron nitride (h-BN) to produce synergistic improvements in radiative cooling performance. Thermal emissivity of differently loaded samples were determined through the use of the FLIR E40 Infrared Thermal Camera and the Stefan-Boltzmann Law. Solar reflectivity in the UV-Visible Near Infrared (UV-Vis NIR) wavelength range was measured using the Perkin Elmer LAMBDA 950 UV-Vis NIR Spectrophotometer. Thermal conductivity was determined using the ai-Phase Mobile M3 Type 1 machine. It was observed that EG fillers had a more significant impact on improving radiative cooling performance compared to h-BN. Comparisons between heating and cooling profile yielded that EG and h-BN had a synergistic coupling effect on improving radiative cooling performance. Formulation containing 2.0wt% EG and 30wt% h-BN exhibited the best cooling power and contributed to the greatest decrease in equilibrium temperatures by 12.6℃.